Hypocomplementemia during tocilizumab treatment - Amir Bieber, MD; Doron Markovits, MD, PhD; Kohava Toledano, MD; Yonit Tavor, MD; Reuven Mader, MD; Alexandra Balbir-Gurman, MD; Yolanda Braun-Moscovici, MD (Medicine, 2022)
Abstract. Hypocomplementemia has been reported in patients with rheumatoid arthritis treated with tocilizumab (TCZ), but its long-term consequences are unknown. We assessed the long-term outcome of patients treated with TCZ who developed hypocomplementemia regarding serious bacterial infections or autoimmune diseases (AID). The charts of patients treated with TCZ at two rheumatology centers were reviewed retrospectively. Data regarding patients’ age, gender, disease duration, autoantibodies status, previous or concomitant treatments, blood counts, liver enzymes, C3 and C4 levels at baseline and during TCZ treatment, episodes of infections, allergic reactions, and AID were analyzed. Univariate analysis was used to compare patients with low C3, C4 levels versus patients with normal C3, C4 levels. Variables that were statistically significant associated or tended to be associated with low C3 or C4 were included in multiple variable logistic regression. Of 132 patients treated with TCZ, 108 had serial measurements of serum complement concentration. Thirty-three (30%) patients developed low C4 levels and 23 (21%) had also low C3. Mean TCZ treatment period was 4.9 years (range, 1–14 years). All patients had normal complement levels at baseline. Leukopenia occurred in 18 (16.7%) patients, 14 of whom (77%) had low complement. Persistent leukopenia was observed in 8% and 5.3% of patients with normal C3 and C4 levels, respectively, as opposed to 47% and 42% of patients with low C3 or low C4, respectively. Low C3, C4 levels correlated with prolonged TCZ treatment retention time and effectiveness. There were no serious bacterial infections or new onset AID. Hypocomplementemia during TCZ treatment was accompanied by leukopenia that correlated with treatment duration. Hypocomplementemia was not associated with serious bacterial infections or new onset AID. Decreased complement levels were associated with treatment longevity. The role of monitoring complement level in predicting treatment response or assessing disease activity deserves further investigation.